Pengaruh Cash Flow Dan Net Working Capital Terhadap Cash Holding Dengan Firm Size Sebagai Variabel Moderating: (Studi Kasus Pada Perusahaan Sektor Aneka Industri yang Terdaftar di Bursa Efek Indonesia Tahun 2017 - 2022) - Hanni Agnesstyaningsih; Desy Nur Pratiwi; Sri Laksmi Pardanawati (Jurnal Ilmiah Keuangan Akuntansi Bisnis (JIKAB), 2023)
This study aims to examine and analyze the effect of Cash Flow (X1) and Net Working Capital (X2) on Cash Holding (Y) with Firm Size (M). The period used in this study is 6 years, starting from 2017-2022. This study uses secondary data in the form of financial reports obtained from the official website www.idx.co.id. Sampling used purposive sampling with a population of 55 companies in various industrial sectors listed on the Indonesia Stock Exchange in 2017-2022 that met the sample criteria of 10 companies. The data analysis method in this study uses 2 data analysis methods, namely multiple linear regression analysis and Moderating Regression Analysis (MRA) with the help of IBM SPSS version 23 software. The results of this study indicate that cash flow and net working capital have a significant positive effect on cash holdings in sector companies. various industries. Meanwhile, the firm size variable is not able to moderate the effect of cash flow and net working capital on the cash holding of companies in various industrial sectors. Keywords: Cash flow, net working capital, firm size, cash holding